Factors associated with COVID-19 booster vaccine willingness among migrants from the Eastern Mediterranean living in Australia: a cross-sectional study - Keeley Allen; Stephen B. Lambert; Aidan Yuen; Davoud Pourmarzi (BMC, 2022)
Abstract Background Migrants have been disproportionally affected by COVID-19 in Australia. Vaccination against COVID-19 is a key pillar of Australia's public health response, but little is known about the willingness to receive booster vaccinations among migrants. This study aimed to assess the factors associated with a willingness to receive a COVID-19 booster vaccine among migrants living in Australia born in the World Health Organization's Eastern Mediterranean Region (EMRO). Methods A cross-sectional survey was conducted from September to November 2021 (n = 300). Participants were questioned on booster vaccine willingness, sociodemographic characteristics, COVID-19 vaccine information needs and sources, and perceptions of COVID-19 vaccines. Univariate and multivariate logistic regression were used to assess factors associated with booster willingness. Results Most respondents (87%) had received two doses of COVID-19 vaccine, of which 81% were willing to receive a booster dose. About half of the participants reported high or very high needs for receiving information about "COVID-19 vaccines' safety monitoring in Australia", "COVID-19 vaccines protection against illness", "Safety of COVID-19 vaccines used in Australia", and "The Australian COVID-19 vaccination program". People who were willing to receive a boost dose had significantly higher self-estimated knowledge of COVID-19 vaccines, confidence in COVID-19 vaccines and trust in the Australian government's vaccine recommendations, and perceived COVID-19 as a greater risk compared to those who were unsure/hesitant. Both groups reported similar perceptions of their personal risks from COVID-19 but diverged on their views of COVID-19 as a broader health problem. There were no statistically significant differences between the two groups in terms of channels used to find information about COVID-19 vaccines. Factors associated with willingness to receive a COVID-19 booster vaccine in the multivariate logistic regression were age (aOR 1.07 95% CI 1.02-1.12), and no exposure to concerning news about COVID-19 vaccines (aOR 3.71 95% CI 1.51-9.09). Conclusion Vaccine acceptance and reported booster willingness was high. The results suggest the news and information seen may impact willingness to receive booster doses, even among those who have already received doses of COVID-19 vaccine. Addressing vaccine concerns and transparent communication about uncertainty should be a priority in the current and in future pandemics.